Olfactory impairment in the rotenone model of Parkinson’s disease is associated with bulbar dopaminergic D2 activity after REM sleep deprivation - Rodrigues, Lais S.; Targa, Adriano D. S.; Noseda, Ana Carolina D.; Aurich, Mariana F.; Da Cunha, Cláudio; Lima, Marcelo M. S. (Frontiers in Cellular Neuroscience, 2014)
Olfactory and rapid eye movement (REM) sleep deficits are commonly found in untreated subjects with a recent diagnosis of Parkinson's disease (PD). Besides different studies reported declines in olfactory performances during a short period of sleep deprivation. Mechanisms underlying these clinical manifestations are poorly understood although the impairment in the dopamine (DA) neurotransmission in the olfactory bulb and in the nigrostriatal pathway may have important roles in olfactory as well as in REM sleep disturbances. Therefore, we have led to the hypothesis that a modulation of the dopaminergic D2 receptors in the olfactory bulb could provide a more comprehensive understanding of the olfactory deficits in PD and after a short period of REM sleep deprivation (REMSD). We decided to investigate the olfactory, neurochemical and histological alterations generated by the administration of piribedil (a selective D2 agonist) or raclopride (a selective D2 antagonist), within the glomerular layer of the olfactory bulb, in rats submitted to intranigral rotenone and REMSD. Our findings provided a remarkable evidence of the occurrence of a negative correlation (r = - 0.52, P = 0.04) between the number of periglomerular TH-ir neurons and the bulbar levels of DA in the rotenone, but not sham groups. A significant positive correlation (r = 0.34, P = 0.03) was observed between nigral DA and olfactory discrimination index (DI), for the sham groups, indicating that increased DA levels in the substantia nigra pars compacta (SNpc) are associated to enhanced olfactory discrimination performance. Also, increased levels in bulbar and striatal DA induced by piribedil in the rotenone control and rotenone REMSD groups were consistent with reduced amounts of DI. The present evidence reinforce that DA produced by periglomerular neurons, and particularly the bulbar dopaminergic D2 receptors, are essential participants in the olfactory discrimination processes, as well as SNpc and striatu